2001
DOI: 10.1111/j.1469-7793.2001.t01-1-00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of lactic acid on force production in rat skeletal muscle

Abstract: During strenuous exercise lactic acid accumulates producing a reduction in muscle pH. In addition, exercise causes a loss of muscle K+ leading to an increased concentration of extracellular K+ ([K+]o). Individually, reduced pH and increased [K+]o have both been suggested to contribute to muscle fatigue. To study the combined effect of these changes on muscle function, isolated rat soleus muscles were incubated at a [K+]o of 11 mm, which reduced tetanic force by 75 %. Subsequent addition of 20 mm lactic acid le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
177
4
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(204 citation statements)
references
References 29 publications
19
177
4
4
Order By: Relevance
“…leg exercise) via an increase in blood lactate (up to 10 mmol l ¡1 ), resulting in reduced performance (Bangsbo et al 1996;Hogan and Welch 1984;Jacobs et al 1993). However, recent studies have shown that muscle performance is enhanced rather than impaired by higher lactate concentrations (Nielsen et al 2001;Pedersen et al 2004). Moreover, in a previous study we did not observe a signiWcant increase in blood lactate concentration as a result of inspiratory resistive breathing at 70% PI max to exhaustion (Rohrbach et al 2003).…”
Section: Methodological Aspectsmentioning
confidence: 74%
“…leg exercise) via an increase in blood lactate (up to 10 mmol l ¡1 ), resulting in reduced performance (Bangsbo et al 1996;Hogan and Welch 1984;Jacobs et al 1993). However, recent studies have shown that muscle performance is enhanced rather than impaired by higher lactate concentrations (Nielsen et al 2001;Pedersen et al 2004). Moreover, in a previous study we did not observe a signiWcant increase in blood lactate concentration as a result of inspiratory resistive breathing at 70% PI max to exhaustion (Rohrbach et al 2003).…”
Section: Methodological Aspectsmentioning
confidence: 74%
“…The activation of glycogen phosphorylase during stress increases the accumulation of lactate and protons and changes ion permeability causing fatigue, and ultimately, pain and distress (Gregory, review 1998;Nielsen, de Paoli, & Overgaard, 2001;Pedersen, Nielsen, Lamb, & Stephenson, 2004). The acidification of the muscles causes changes in ion balance which leads to attenuation of the rate of glycolysis, because protons inhibit the activities of glycogen phosphorylase and phosphofructokinase and thus energy production from carbohydrates (Fitts, review 1994;Nielsen, de Paoli, & Overgaard, 2001;Pedersen, Nielsen, Lamb, & Stephenson, 2004). Protons may also inhibit the function of myosin ATPase (Fitts, review 1994;Schiaffino & Reggiani, review 1996) and thus impair muscle contractions.…”
Section: The Formation Of Lactatementioning
confidence: 99%
“…with lactate against muscular fatigue [32]. It must take in account that a bottle of PJ contains while MDA levels were not affected after four weeks of pomegranate juice consumption [19].…”
mentioning
confidence: 99%